2008
DOI: 10.1177/1062860607310916
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Early Hospital Readmission in Patients With Congestive Heart Failure

Abstract: Little is known about factors related to rehospitalizations that occur soon after discharge in patients with congestive heart failure (CHF). The aim of this study was to determine if there are specific characteristics common to CHF patients readmitted within 30 days. Study methods included retrospective chart review. Patients included all those hospitalized and readmitted to a large community teaching hospital for CHF exacerbation within 30 days between January 7, 2005 and June 30, 2006. A total of 58 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 29 publications
0
31
0
3
Order By: Relevance
“…28 Claims-based algorithms may overestimate the preventability by not fully accounting for patient characteristics (eg, severity of chronic condition) and planned readmissions. 29,30 Medical record review, on the other hand, may provide added clinical detail but may be limited in ascertaining the contribution of sociodemographic characteristics that may not be documented in the medical record (eg, unmet social needs, medication adherence) or may occur outside of the hospital (eg, missed appointments, transportation barriers), thereby leading to underestimation of the likelihood of preventability. 13, 25, 31 -34 Interviews in combination with medical record review may provide a more global understanding of these circumstances leading up to, and after, a child's hospitalization.…”
Section: Figurementioning
confidence: 99%
“…28 Claims-based algorithms may overestimate the preventability by not fully accounting for patient characteristics (eg, severity of chronic condition) and planned readmissions. 29,30 Medical record review, on the other hand, may provide added clinical detail but may be limited in ascertaining the contribution of sociodemographic characteristics that may not be documented in the medical record (eg, unmet social needs, medication adherence) or may occur outside of the hospital (eg, missed appointments, transportation barriers), thereby leading to underestimation of the likelihood of preventability. 13, 25, 31 -34 Interviews in combination with medical record review may provide a more global understanding of these circumstances leading up to, and after, a child's hospitalization.…”
Section: Figurementioning
confidence: 99%
“…Associated diagnosis of anemia, hypertension, and diabetes confer higher risk and are likely indicator of disease progression and are predictors of re-admissions and mortality [6,10,26,28,40]. Comorbidity has been shown as a predictor of unplanned readmission [41]. In addition, comorbidities were associated with increasing readmission in >80 year old within 30 days with comorbidities odds ratio = 2.6; 95% CI, 1.5-4.7 [42].…”
Section: Literature Reviewmentioning
confidence: 89%
“…[9] Subsequently, a retrospective manual chart review at a large community teaching hospital found that focusing on renal failure alone could lead to major improvements in readmission rates. [10] Telehome monitoring was also found to reduce the number of readmissions and to improve functional status, leading to better quality of life. [11] In the mid-2000's, readmission reduction strategies gained a process improvement perspective, which involved an integrated delivery system model, process redesign, evidencebased practices, a multidisciplinary approach, and real time data collection.…”
Section: Evolution Of Readmission Reduction Strategiesmentioning
confidence: 99%